Crystal structures of complexes of mouse thymidylate synthase crystallized with N4-OH-dCMP alone or in the presence of N5,10-methylenetetrahydrofolate - Dowierciał Anna; Jarmuła Adam; Wilk Piotr; Rypniewski Wojciech; Kierdaszuk Borys; Rode Wojciech (Pteridines, 2013)
To solve the inhibition mechanism of thymidylate synthase (TS) by N4-hydroxy-dCMP (N4-OH-dCMP), crystallographic studies were undertaken. Structures of three mouse TS (mTS) complexes with the inhibitor were solved, based on crystals formed by the enzyme protein in the presence of either only N4-OH-dCMP [crystal A, belonging to the space group C 1 2 1, with two monomers in asymmetric unit (ASU), measured to 1.75 Å resolution] or both N4-OH-dCMP and N5,10-methylenetetrahydrofolate (mTHF) (crystals B and C, both belonging to the space group C 2 2 21, each with a single monomer in ASU, measured to resolution of 1.35 Å and 1.17 Å, respectively). Whereas crystal A-based structure revealed the mTS-N4-OH-dCMP binary complex, as expected, crystals B- and C-based structures showed the enzyme to be involved in a ternary complex with N4-OH-dCMP and noncovalently bound dihydrofolate (DHF), instead of expected mTHF, suggesting the inhibition to be a consequence of an abortive enzyme-catalyzed reaction, involving a transfer of the one-carbon group to a hitherto unknown site and oxidation of THF to DHF. Moreover, both C(5) and C(6) inhibitor atoms showed sp3 hybridization, suggesting C(5) reduction, with no apparent indication of C(5) proton release. In accordance with our previous results, in all subunits of these structures the inhibitor molecule was identified as the anti rotamer of imino tautomer, forming, similar to deoxyuridine monophosphate, two hydrogen bonds with a conservative asparagine (mouse Asn220) side chain.